Contrast induced acute kidney injury and the role of beta-blockers in its prevention - Barbero, Umberto; Iannaccone, Mario; De Benedictis, Michele; Doronzo, Baldassarre (Journal of Thoracic Disease, 2019)
Contrast-induced acute kidney injury (CI-AKI) is a well-known plight after diagnostic or interventional procedures requiring iodinated contrast media. It is actually the third cause of renal breakdown in hospitalized patients, and an everyday concern for procedures with high contrast use like coronary angioplasty (1).